Aims, programs, and effects of altitude training in different top sport disciplines - Matsin, T.; Alaver, M.; Lemberg, H. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Altitude training and the effect it has on athletic performance continues to be a topic of controversy among athletes, coaches, and sport scientists. The purpose of this study is to improve the understanding of the physiological responses and adaptations of top level athletes in various disciplines at different altitudes, as well as the ways in which these physiological adaptations may influence performance.